Pengaruh Matrikulasi Matematika Dasar Terhadap Peningkatan Kemampuan Matematika Dasar Pada Mahasiswa Baru Jurusan Fisika - Muhammad, Al Jalali (Jurnal Penelitian Pendidikan Fisika, 2021)
Department of Physics is a department that has a distribution of subjects that require good mathematical skills in order to understand lecture topics. Matriculation is one solution to equip students with basic knowledge of mathematics in the Physics. Matriculation is a learning activity to increase students knowledge before starting an educational program. In this program, research on basic mathematical matriculation has been carried out as an effort to improve the basic mathematics skills of new students of the Department of Physics, Faculty of Mathematics and Natural Sciences, UHO Academic Year 2020/2021. The research was conducted due to many complaints from lecturers regarding the weak basic mathematics skills of students. In this study, the matriculation activity has improved the students basic math skills with an effectiveness value is 39%, from 3 people passing the pre test to 12 passing the post test.